(3QSGdI aj CbhGd GdYdeGA aj eZGdWI GdLPQ GdCUes - (3CMeO GdThbj (B((3cPG (B)s
(3ChdgG (B:s
(3HSe Gddg GdMeO ddg QH GdYGdejf CQOJ Cf CLeY CbhGd GdYdeGA aj GdeZdWI GdJj SeGgG UGMH TQM GdebGUO (B( (3GdLPQ GdCUe (B) (3GdJj JMjQ aj MdgG Ybhd GdYbdGA haMhd GdCPcjGA s
(3BNQgG (B:s
(3Ef GdaYd GdhGMO bO jchf MSfG aj ecGf hbO jchf bHjMG aj ecGf BNQ cGdaYd GdhGbY aj GdeSLO hNGQLg GfJgi hddeZdWI GdeTghQI fXeJ GdCbhGd GdefKhQI aj gPg GdQSGdI GdeRHhQI hddg GdMeOs
(3QHeG cGfJ HNW eDdagGs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdadSaI hGdefWbs